Promising activity of concave Pd@Pd-Pt nanocubes for the oxygen reduction reaction. (1st February 2017) - Liu, Zhe-Ting; Chen, Ho-Rei; Lee, Chien-Liang
Graphical abstract: Highlights: The concave and defective Pd@Pd-Pt nanocubes (NCs) are prepared. A Pt layer is predominantly deposited at the corners and edges of Pd NCs. Pd@Pd-Pt NCs show a 1.7-fold higher activity than did Pt catalyst. Abstract: Defective Pd@Pd-Pt nanocubes (NCs) were successfully synthesized by a displacement deposition method. In this study, a Pt layer was predominantly deposited at the corners and edges of Pd NCs to form concave NC surfaces and a Pd-Pt shell with a Pd-only core. Additionally, rotating ring-disk electrode experiments were performed to determine the mass activities of these Pd@Pd-Pt NCs, which acted as oxygen reduction catalysts in a KOH solution. The concave Pd@Pd-Pt NCs (28.2 nm) exhibited a 1.7-fold higher activity than that of 7 nm Pt nanoparticles. After accelerated durability tests, the data indicated the prepared NCs retained nearly 80% of the initial activity for the oxygen reduction reaction.